PERAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA MODERN - Anik Sholichatul (PT. Habe Cendekia Utama, 2025)
Digital technology has significantly transformed the education sector, changing teaching, administration, and evaluation methods. This research aims to explore the role of digital technology in modern education, providing insights for educators, students, and policymakers on technology integration in education. Research on digital technology in education can be conducted using experimental or quasi-experimental designs, involving dividing students into an experimental group using digital technology and a control group using traditional methods. Digital technology has transformed education by making the learning process more flexible, personalized, and collaborative. This technology supports self-directed learning, increases student motivation, and provides access to a variety of learning resources. Innovations such as LMS, e-learning, VR/AR, and AI-based adaptive learning systems enhance learning methods and meet student needs, improve learning outcomes, and develop 21st-century skills.